Public-private partnerships : case studies on infrastructure development - Levy, Sidney M. (ASCE Press, 2011)
This book demystifies the innovative solution to the challenges of designing, financing, building, and operating major infrastructure projects. In today's world, partnerships between public agencies - federal, state, and local - and private companies are an increasingly popular policy tool. At a time when infrastructure in the United States and elsewhere is aging and public budgets are shrinking, public-private partnerships (PPPs) permit planners to leverage limited funds, while private firms embrace these relationships as an unfolding and potentially profitable global market. But what separates a successful partnership from one that fails to deliver on its promise? In this book, the author brings a balanced perspective to the history and development of the PPP movement. He outlines different approaches to defining and planning a PPP, supplemented by a history of PPP toll roads in the United States. He describes the key players in a PPP deal and provides case studies of projects in Virginia, Illinois, Florida, Canada, and Mexico. This compendium of practical detail on public-private partnerships is essential reading for civil engineers, engineering managers, construction contractors, developers, and government officials involved in or contemplating a major infrastructure project. -- Provided by publisher.
Keywords: Public-private sector cooperation -- United States -- Case studies.; Infrastructure (Economics) -- United States -- Case studies.; Public works -- United States -- Case studies.; elektronické knihy; electronic books